From the investigative pedagogical practice of deepening to the training of future licensed FESAD. - Bustamante Parra, Andrea Catalina; López Valiente, Erika Johana (Universidad Pedagógica y Tecnológica de Colombia, 2022)
This research article shows an analysis of the Pedagogical and Investigative Practice of Deepening (PPIP), carried out in the first semester of 2019, in the Bachelor of Basic Education with an emphasis in Mathematics, Humanities and Spanish Language, Faculty of Distance Studies of the Pedagogical and Technological University of Colombia, in order to characterize the practice process of teachers in training. Therefore, for this study, the qualitative approach prevailed, which included the survey as the main instrument. The methodological process of the research revolved around the experiences and the role played by the students of the tenth semester of the Bachelor’s degree in the different educational institutions of which they were part, where it was possible to demonstrate from their work the development of the Pedagogical project of Classroom in the educational setting with mistakes and successes of the experience in different educational settings. Finally, the authors can concluded that teachers in training, according to their context, seek to respond to the needs of their diversity by applying the knowledge acquired during their teaching training in the Bachelor’s Degree.